Forty‐eight hour kidney transplant admissions. (27th June 2013) - Siskind, Eric; Villa, Manuel; Jaimes, Natalia; Huntoon, Kristin; Alex, Asha; Blum, Mark; Tyrell, Richard; Sameyah, Emil; Kuncewitch, Michael; Giangola, Matthew; Agorastos, Stergiani; Deutsch, Gary; et al.
Abstract Forty‐eight hour kidney transplantation admissions are a feasible option in selected recipients of live‐donor allografts through the use of standardized post‐operative protocols, multidisciplinary team patient care, and intensive follow‐up at outpatient centers. Age, gender, and pre‐transplant dialysis status did not impact the ability to achieve 48‐hour admissions. We did not identify any other pre‐operative risk factors that contributed to increased length of stay. Although ABO and highly sensitized recipients had longer lengths of stay, the subgroup was too small to achieve statistical significance. We did not encounter any readmissions within the first seven post‐operative days. Further improvements in clinical management will enhance the potential to shorten the length of hospital stay for all kidney transplant recipients.